(untitled) (Nexus International Journal of Science and Education, 2024)
This study unfolded the extent of the planning technique of a reading coordinator and its association with support to literacy development among Elementary Learners in Mati South District, Mati City Schools Division. The study used a non-experimental descriptive-correlational research design, where it utilized an adapted survey instrument to gather responses from the randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that planning techniques of reading coordinators in terms of communicating with parents and administrators, collaborating with teachers, planning, and implementing the reading program, and providing individualized support are extensive, while support to literacy development among elementary learners in terms of comprehension, phonemic awareness, vocabulary, phonics, Fluency, and writing is moderately extensive. There was a significant relationship between the planning techniques of a reading coordinator and literacy development among elementary learners. Domains of teachers' pedagogical skills in terms of collaboration with teachers, planning and implementing reading programs, providing individualized support, analyzing data and communicating with parents and administrators significantly influenced literacy development. Future research may engage in partnerships to implement and evaluate interventions aimed at enhancing planning mechanism skills.